Evaluation on Numerical Method of Differential Formula Based on Optimal Control of Space Robot's Attitude and Motion - Bu, Bing (Informatica, 2024)
Due to the complexity of the space robot system structure and working environment, various noises and friction torque between the joints of the manipulator and sloshing of liquid fuel, etc., uncertainty and external disturbance are inevitable. If these factors are not considered in the control system design, the accuracy and stability of the controlled system would not be guaranteed. In this paper, the robust trajectory tracking control of a space robot system with a base attitude controlled under the conditions of uncertainty and external disturbance was studied respectively. In this paper, for the space robot system with uncertainty, a robust trajectory tracking controller design method based on the optimal control differential formula of space robot attitude motion was proposed, and the uncertainty of the space robot system was analyzed. The quasi-linear structure of the system was obtained by analyzing the two uncertainty functions numerically by means of differential formulas. Combining the robust performance index with the optimal control formula of attitude motion, a robust optimal controller was obtained. Taking the optimal path obtained by optimization as an example, simulations were carried out for the space robot system with uncertainty and external disturbance respectively. When N was 160 cycles, the angles of each joint were 41°, 76° and 10°, so the planning in this paper is feasible. The optimal control scheme of space robot attitude motion proposed in this paper not only improved the robustness, but also reduced the pose disturbance caused by the motion of the manipulator to the base vehicle.